Association of alcohol consumption and aortic calcification in healthy men aged 40–49 years for the ERA JUMP Study. (January 2018) - Mahajan, Hemant; Choo, Jina; Masaki, Kamal; Fujiyoshi, Akira; Guo, Jingchuan; Hisamatsu, Takashi; Evans, Rhobert; Shangguan, Siyi; Willcox, Bradley; Okamura, Tomonori; Vishnu, Abhishek; Barinas-Mitchell, Emma; et al.
Abstract: Background and aims: Several studies have reported a significant inverse association of light to moderate alcohol consumption with coronary heart disease (CHD). However, studies assessing the relationship between alcohol consumption and atherosclerosis have reported inconsistent results. The current study was conducted to determine the relationship between alcohol consumption and aortic calcification. Methods: We addressed the research question using data from the population-based ERA-JUMP Study, comprising of 1006 healthy men aged 40–49 years, without clinical cardiovascular diseases, from four race/ethnicities: 301 Whites, 103 African American, 292 Japanese American, and 310 Japanese in Japan. Aortic calcification was assessed by electron-beam computed tomography and quantified using the Agatston method. Alcohol consumption was categorized into four groups: 0 (non-drinkers), ≤1 (light drinkers), >1 to ≤3 (moderate drinkers) and >3 drinks per day (heavy drinkers) (1 drink = 12.5 g of ethanol). Tobit conditional regression and ordinal logistic regression were used to investigate the association of alcohol consumption with aortic calcification after adjusting for cardiovascular risk factors and potential confounders. Results: The study participants consisted of 25.6% nondrinkers, 35.3% light drinkers, 23.5% moderate drinkers, and 15.6% heavy drinkers. Heavy drinkers [Tobit ratio (95% CI) = 2.34 (1.10, 4.97); odds ratio (95% CI) = 1.67 (1.11, 2.52)] had significantly higher expected aortic calcification score compared to nondrinkers, after adjusting for socio-demographic and confounding variables. There was no significant interaction between alcohol consumption and race/ethnicity on aortic calcification. Conclusions: Our findings suggest that heavy alcohol consumption may be an independent risk factor for atherosclerosis. Highlights: Alcohol consumption has a J-shaped association with CHD. Studies reported conflicting relationships between alcohol consumption and atherosclerosis. We cross-sectionally examined the relationship between alcohol consumption and aortic calcification. The heavy alcohol consumption was positively associated with aortic calcification. Moderate alcohol consumption may lower CHD risk through mechanisms other than reduced atherosclerotic lesion calcification.